Modeling of carbon black filled natural rubber vulcanizates by the standard triboelastic solid - Coveney V A; Johnson D E (Rubber Chemistry and Technology, 1999)
Mathematical modeling of the dynamic behaviour of vulcanizates is reviewed with the emphasis on carbon black filled natural rubber(NR). The 3 constant standard triboelastic solid (STS) model and its behaviour are described, in general terms and with specific reference to low frequency shear data for a wide range of filled NR vulcanizates. Good general agreement is found between model and experiment for the data obtained at strain amplitudes down to 0.01; there is also acceptably good correlation between carbon black loading and values of STS constants.
Keywords: Carbon black filled NR; Triboelastic solid